Public policies and the misuse of forest resources - Repetto, Robert C.; Gillis, Malcolm (A World Resources Institute book, 1988)
This book documents how government policies affecting taxation, credit, timber concessions, and public investment contribute to deforestation and the misuse of forest resources in both the developing and the developed worlds. Ten case studies - of the United States, Braxil, China, the Phillipines, Indonesia, Malaysia, Liberia, Ghana, Gabon, and the Ivory Coast - show how forests have bben sacrificed to make quick profits and how many such ventures are intrinsically uneconomic but are supported by generous public subsidies. The authors argue that deforestation results not just from population growth or landlessness, but also from misguided government decisions. They convincingly describe the serious fiscal and economic losses such decisions entail and propose policy changes that can preserve forest resources without interfering with other economic objectives.